The effect of Applying (E-learning) in Higher Education: Study on a Number of Students from different Universities in Iraq - Hasan, Ibrahim Naeem; abd-alrazak, Maryam Qutaiba; Rashid, Shatha Talib (Journal of Research in Social Science and Humanities, 2023)
COVID-19’s pandemic has hastened the expansion of online learning across all levels of education. Countries have pushed to expand their use of distant education and make it mandatory in view of the danger of being unable to resume face-to-face education. This study aims to determine the challenges and obstacles face by students in Iraqi universities with e-learning. It founds that the main problems that influence and impact online learning during COVID-19 are related to technical, academic, and communication challenges. The study results show that a total of 39.89% agreed that e-learning facilitates the learning process from various aspects, and a total of 42.13% disagreed with that, and a total of 17.8% are moderate.